العوامل المؤثرة على تحويل التلاميذ من التعليم العام إلى التعليم الأزهري ومتطلبات تنظيمها - أحمد، فاطمة مصطفى عبدالهادي السعيد; المهدي، مجدي صلاح طه; الدياسطي، مروة بكر مختار (جامعة المنصورة - كلية التربية, 2023)
تعتبر المعاهد الأزهرية من المؤسسات التعليمية الرائدة في مجال التعليم الديني، فهي تسهم في توفير التعليم الأزهري لمليوني طالب وطالبة في مصر والعالم، وتقوم بدور بارز في تعميق روح الانتماء والولاء للدين والوطن، من خلال برنامج تعليمي يهدف إلى بناء الشخصية الإسلامية الوسيطة، غير أن هناك تغيرات مجتمعية نالت من مكانة هذا التعليم، ولا شك أن هناك عوامل مؤثرة في الإقبال الكبير على المعاهد الأزهرية منها ما هو متعلق بالتعليم العام، ومنها ما هو متعلق بالتعليم الأزهري، ويهدف البحث الحالي إلى الوقوف على تلك العوامل المؤثرة على تحويل التلاميذ من التعليم العام إلى التعليم الأزهري ومتطلبات تنظيمها. Spirit Al-Azhar institutes are considered one of the leading educational institutions in the field of religious education. They contribute to providing Al-Azhar education to two million male and female students in Egypt and the world, and they play a prominent role in belonging and loyalty to religion and the homeland through an educational program aimed at building the intermediate Islamic personality. However, there are changes. There is no doubt that there are factors influencing the great demand for Al-Azhar institutes, some of which are related to general education, and some of which are related to Al-Azhar education. The current research aims to identify those factors influencing the trans of students from general education to public education. Al-Azhar and its organization requirements.
Keywords: التعليم العام -- التعليم الأزهري -- تحويل الطلاب -- مصر